A Cross-sectional Study of Antiglaucoma Drug Utilisation and Prescribing Patterns in a Tertiary Care Hospital, Udaipur, Rajasthan, India - Swati Jangir; Bipa Mazumdar; (Col) Avinash Mishra (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Glaucoma is one of the leading causes of irreversible blindness worldwide and requires long-term pharmacological management. Drug utilisation studies help evaluate prescribing patterns, rational drug use, treatment adherence, and cost-related factors in glaucoma management. Aim: To evaluate the utilisation pattern of antiglaucoma medications and prescribing trends in a tertiary care hospital, Udaipur, Rajasthan, India. Materials and Methods: The present cross-sectional study was conducted in the Ophthalmology Outpatient Department (OPD) at American International Institute of Medical Sciences, a Tertiary Care Institution, Udaipur, Rajasthan, India, from December 2024 to December 2025. A total of 127 patients diagnosed with glaucoma were included in the study. Data regarding demographic characteristics, clinical profile, prescribed medications, treatment patterns, dosing frequency, duration of therapy, and generic versus branded prescribing were collected using patient interviews and prescription records. Statistical analysis was performed using descriptive statistics and the Chi-square test. A p-value